Marc Riboud and the Truth About Flowers - Eftimov, Yordan (Media and Language, 2020)
The article links the metaphorical image of flowers to the 1957 Chinese political campaign “100 Flowers” and the anti-war “Flower Power” movement in the United States in the mid-1960s. The focus in the article is on the acute experience, that is, on the imagery of the world in our mind, on the perception of reality shaped by memory, as well as on the prefunctionalization of the floral metaphor.